Soil Health Card an initiative for conserving natural resources and enhancing farm profit - Dwivedi, Vandana (Indian Farming, 2018)
The widening of nutrient-demand supply gap, affects nutrient use efficiency and economic returns. Therefore, it becomes necessary to have an improvement in soil health monitoring system on one hand and enhancing farmer’s awareness about soil health and its management. Providing soil health cards to the farmers actually immerged out of this necessity.